Optimal time-fixed impulsive non-Keplerian orbit to orbit transfer algorithm based on primer vector theory - Bucchioni, Giordana; Gemignani, Gabriele; Lombardi, Francesco; Bellome, Andrea; Leitão, João Pedro Fernandes; Lizy-Destrez, Stèphanie; Innocenti, Mario (Elsevier, 2023)
The work applies a systematic method to compute an optimal transfer trajectory between two non-Keplerian halo orbits in the Circular Restricted Three-body formulation of the Earth–Moon dynamics. The paper exploits the knowledge of the natural non-linear dynamics and the primer vector theory applied to the Circular Restricted Three Body Problem to design optimal multi-impulsive Halo-to-Halo transfers with fixed and limited Time of flight, from every point of the departure orbit to every point of the arrival orbit with an optimal number of impulses. The used method is constituted by three systematic steps with the goal of facilitating the mission design process and the on-board autonomous guidance implementation of future missions in highly non-linear dynamics.
Keywords: CR3BP; HaloTransfer; Optimisation; Astrodynamics